Development and validation of nomograms for predicting grade ≥3 diarrhea and neutropenia after abemaciclib combined with endocrine therapy for breast cancer: a multicenter retrospective real-world study - Wang, Lei; Yang, Siyuan; Zhang, Ji; Wang, Hairui; Zhang, Ying; Wang, Xin; Shen, Meng; Ye, Chunmei; Deng, Taiwen; Ying, Yujin; Li, Yang; Nie, Jianyun (Frontiers in Oncology, 2025)
BackgroundThis study aimed to investigate the risk factors associated with grade ≥3 diarrhea and neutropenia, which are the most common adverse events (AEs) leading to discontinuation and dose reduction in patients with hormone receptor-positive (HR+)/human epidermal growth factor 2-negative (HER2-) breast cancer treated with cyclin-dependent kinase 4/6 (CDK4/6) inhibitor abemaciclib combined with endocrine therapy (ET). Subsequently, two prediction nomograms were developed to serve as a foundation for enhancing the management of patients’ side effects and improving treatment quality.MethodsA retrospective cohort analysis was conducted to explore the clinical characteristics and treatment variables of breast cancer patients treated with abemaciclib combined with ET in Yunnan Cancer Hospital from December 2021 to December 2022. Logistic regression was used to determine the risk factors for the occurrence of grade ≥3 diarrhea and neutropenia, and two kinds of nomograms were established. An external validation group of patients from three additional centers was used to validate the constructed nomograms. The area under the receiver operating characteristic (ROC) curve (AUC), calibration curve, and decision curve analysis (DCA) were used to assess the predictive performance and clinical applicability of the two nomograms.ResultsA total of 497 patients were included, including 403 in the modeling group and 94 in the external validation group. The results of the multifactorial analysis revealed that age ≥70 years, Eastern Cooperative Oncology Group (ECOG) score ≥1, and underlying gastrointestinal diseases were independent risk factors for grade ≥3 diarrhea. ECOG score ≥1, radiotherapy in the same period/within 1 month, and neutrophils ≤2.0×109/L before treatment were independent risk factors for grade ≥3 neutropenia. Two nomogram models were used to predict risk based on the above independent factors. The AUCs for the developmental and external validation groups were 0.747(95%CI:0.687-0.806) and 0.803(95%CI:0.702-0.918) for the diarrhea prediction nomogram and 0.765(95%CI:0.711-0.818) and 0.783(95%CI:0.691-0.892) for the neutropenia prediction nomogram, respectively. Calibration curves and DCA of both models also showed good predictive performance and clinical applicability.ConclusionWe identified risk factors for grade ≥3 diarrhea and neutropenia in patients treated with abemaciclib combined with ET, and established a risk prediction nomogram, providing a scientific basis for safety assessment.